The Development of ISafe Mobile Application Using Messaging and GPS System - Azizi, Nur Afrina Aida; Zainal, Nurezayana (Applied Information Technology And Computer Science, 2021)
Women's safety is a crucial issue in Malaysia as well as other countries. We are all aware of the importance of women's security, but we must acknowledge that they need to be adequately secured as women always have difficulty to request for help whenever they confronting a critical situation such as rape, robbery, and domestic violence. Since individuals using mobile phones have increased rapidly, a smartphone can therefore be used effectively for personal protection or various other security purposes. Thus, the iSafe Mobile Application Using Messaging and GPS System Application are developed to prevent the threats that might occur to women. This application includes an emergency trigger and GPS combination of messages. It can help to identify the victim's position through a GPS and quickly send a message to help them in unexpected circumstances including the location URL to their registered contacts. The system will be developed by using Android Studio and SQLite as database software. The Rapid Application Development (RAD) methodology is used as a system development methodology. The development of this security system will provide women a reliable way to deal with the problem of security issues using messaging and a GPS-based system.